Practical Django Projects, Second Edition - Bennett, James (Apress, 2012)
The past few years have seen an explosion in the development of dynamic, databasedriven web sites. Whereas many sites were once built using nothing but hand-written HTML, or a few CGI scripts or server-side includes, today’s database-backed web applications have become the norm for everything from personal blogs to online stores to the social networking sites that have revolutionized the way many people use the Web. But this has come at a cost. Developing these applications, even for relatively simple uses, involves a significant amount of complex work, and much of that work ends up being repeated for each new application. Although web developers have always had access to libraries of code that could automate certain tasks, such as HTML templating or database querying, the process of bringing together all the necessary pieces for a fully polished application has largely remained difficult and tedious.